A novel case of lupus nephritis and mixed connective tissue disorder in a COVID-19 patient. (June 2022) - Ali, Sajjad; Almas, Talal; Zaidi, Ujala; Ahmed, Farea; Shaikh, Sufyan; Shaikh, Fathema; Tafveez, Rida; Arsalan, Maaz; Antony, Ishan; Antony, Meetty; Tahir, Burhanuddin; Aborode, Abdullahi T.; et al.
Abstract: Introduction: Mixed connective tissue disease (MCTD) is a rare autoimmune condition characterized by Scleroderma, Polymyositis, and Systemic Lupus Erythematous (SLE). Though a possible relationship between COVID-19 and autoimmune diseases has been recently reported, its pathophysiological mechanism behind flares in Lupus Nephritis (LN), a complication of SLE, remains unknown. Case presentation: A 22-year-old COVID-19 positive female presented with anemia, bilateral pitting edema, periorbital swelling, and posterior cervical lymphadenitis. Further inspection revealed lower abdominal striae, hepatosplenomegaly, and hyperpigmented skin nodules. Complete blood counts showed elevated inflammatory markers and excessively high protein creatinine ratio. Antinuclear antibody titers were elevated (anti-smith and U1 small nuclear ribonucleoprotein) and Rheumatoid Factor was positive. She was diagnosed with MCTD associated with a flare of LN. To control her lupus flare, a lower dose of steroids was initially administered, in addition to oral hydroxychloroquine and intravenous cyclophosphamide. Her condition steadily improved and was discharged on oral steroid maintenance medication. Discussion: We present a rare phenomenon of newly diagnosed LN, a complication of SLE, with MCTD in a PCR-confirmed COVID-19 patient. The diagnostic conundrum and treatment hurdles should be carefully addressed when patients present with lupus and COVID-19 pneumonia, with further exploration of the immuno-pathophysiology of COVID-19 infection in multi-systemic organ dysfunction in autoimmune disorders. Conclusion: In COVID-19 patients with LN and acute renal injury, it is critical to promptly and cautiously treat symptomatic flares associated with autoimmune disorders such as SLE and MCTD that may have gone unnoticed to prevent morbidity from an additional respiratory infection. Highlights: SLE disease has been associated with COVID-19. However, there is a lack of data on LN in conjunction with MCTD in COVID-19 positive patients. A possible relationship between Coronavirus disease 2019 (COVID-19) and autoimmune disease has been documented in many case reports. Because of the overlapping clinical manifestations and laboratory findings between lupus and COVID-19 pneumonia, the diagnostic problems and treatment hurdles should be carefully addressed. In COVID-19 patients with LN flare and acute renal injury, it is critical to resolve any reversible causes of the kidney injury and manage the COVID-19 before treating the LN.